Assessing the Impact of Global Sustainability Competitiveness on Logistics Performance: A Regression Study - Ang Dy Pay, Georgiana L. (Philippine Engineering Journal; Vol 45 No 02 (2024), 2024)
Abstract – Logistics performance is impacted by global competitiveness. However, global competitiveness must be sustainable to truly be considered competitive. Therefore, there is a need to assess logistics performance in terms of a metric that encompasses both competitiveness and sustainability. This was proposed to be done through the Global Sustainability Competitiveness Index (GSCI). The objective of this study was to determine whether the GSCI, particularly through its sub-indices of natural capital, resource intensity, social capital, intellectual capital, and governance, has a significant impact on logistics performance (measured through the Logistics Performance Index or LPI). Data from 122 countries for the years 2016, 2018, and 2023 were analyzed through panel data regression analysis, and it was found that the GSCI sub-indices of social capital, intellectual capital, and governance had a positive and statistically significant impact to logistics performance. Therefore, if countries wish to improve on their logistics performance, they may look into improvement of these three factors.   Keywords : logistics performance index, LPI, global sustainability competitiveness index, GSCI, social capital, intellectual capital, governance, panel data regression